Comparison of Bacterial Community Structure and Diversity in Traditional Gold Mining Waste Disposal Site and Rice Field by Using a Metabarcoding Approach - Fatimawali; Billy Johnson Kepel; Maria Apriliani Gani; Trina Ekawati Tallei (International Journal of Microbiology)
Traditional small-scale gold mining mostly use mercury to extract the gold from ores. However, mercury contamination in the environment can affect the composition and structure of the bacterial community. The purpose of this study was to determine the effect of mercury contamination on the bacterial community in the traditional gold mining waste disposal site and in the rice field. Mercury analysis was carried out using the CVAFS method. Analysis of bacterial communities and structure was carried out based on the results of metabarcoding of the V3-V4 16S rRNA regions obtained from paired-end Illumina MiSeq reads. The results showed that the sample from the mining waste disposal site had a mercury level of 230 mg/kg, while the sample from the rice field had 3.98 mg/kg. The results showed that there were differences in microbial composition and community structure in both locations. With the total reads of 57,031, the most dominant phylum was Firmicutes in the mining disposal site sample. Meanwhile, with the total reads of 33,080, the sample from rice field was dominated by Planctomycetes. The abundant classes of bacteria in the mining waste disposal site, from the highest were Bacilli, Gammaproteobacteria and Planctomycetia, while the sample from the rice field was dominated by the Planctomycetia and Acidobacteria subdivision 6. The families that dominated the sample in disposal site were Bacillaceae and Aeromonadaceae, while the sample from the rice field was dominated by Gemmataceae. The abundant genera in both locations were Bacillus and Gemmata. This study concluded that the high level of mercury in the soil reduced the richness and diversity of bacterial phyla and lower taxa. There was also a shift in the dominance of phyla and lower taxa in both locations. This study provides an understanding of the microbial community structure in the area that is highly contaminated with mercury to open insight into the potential of these bacteria for mercury bioremediation.